2019
DOI: 10.3390/met9020199
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Mechanical Strength in Post Heat Treated SLM 2507 at Room and High Temperature Promoted by Hard/Ductile Sigma Precipitates

Abstract: Duplex stainless steel, 71 wt.% austenite, 13 wt.% ferrite and 16 wt.% sigma, was made upon heat treating of fully ferritic as-built selective laser melted (SLM) 2507 stainless steel at 1200 °C. Formation of sigma phase in the heat treated SLM 2507 was investigated using optical microscopy and scanning electron microscopy (SEM). The heat treated SLM 2507 demonstrated a yield strength of 686 MPa, ultimate tensile strength of 920 MPa and an elongation of 1.8% at room temperature with a brittle fracture morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…A post-heat treatment of LPBF 2507 DSS can impart UTS values (920 MPa) higher than that of as-cast and solution-treated (* 600-800 MPa) [181]. This is due to precipitation of Mo-/Cr-rich intermetallic phases (mainly r and v).…”
Section: Alloymentioning
confidence: 96%
“…A post-heat treatment of LPBF 2507 DSS can impart UTS values (920 MPa) higher than that of as-cast and solution-treated (* 600-800 MPa) [181]. This is due to precipitation of Mo-/Cr-rich intermetallic phases (mainly r and v).…”
Section: Alloymentioning
confidence: 96%
“…The post-deposition heat treatment of duplex stainless steel S31803 SLM samples is shown to recover to the desired duplex austenite/ferrite microstructure partially in the range of 900-1200 °C. Maximum γ-fraction (~ 24%) is obtained with heat treatment at 1000 °C for 5 min [233]. Saeidi et al [105] conducted post-deposition heat treatment of 316L SS at various temperatures for 6 min, followed by furnace cooling.…”
Section: Reproduced With Permission From Elseviermentioning
confidence: 99%
“…Saeidi et al in [118] revealed that as-built L-PBF 420 alloy is characterized by a cellular microstructure of micron-sized martensitic cells (as can be seen in [118]); this feature leads to high values of ultimate tensile strength (according to Table 5). Duplex samples processed in L-PBF systems were mainly studied by Hengsbach et al [146] and Saeidi et al in [118,147]. The most relevant observations were:…”
Section: Other Stainless Steel Gradesmentioning
confidence: 99%